The Influence of Decentration on Higher-Order Aberrations in Artisan Aphakic Intraocular Lens Implantation Eyes - Aizhu Miao; Min Zhang; Tianhui Chen; Yi Lu (Journal of Ophthalmology)
Purpose. To characterize the influence of decentration on higher-order aberrations of Artisan aphakic intraocular lens implantation eyes. Setting. Department of Ophthalmology and Vision Science, Eye and ENT Hospital of Fudan University, Shanghai, China. Design. Retrospective case series. Methods. Twenty-three eyes of 18 patients were retrospectively examined. Location of the IOL was imaged using a slit-lamp, and decentration (the distance from the center of a pupil to the geometric center of the IOL) was measured using the AutoCAD 2007 software. Ocular and internal higher-order aberrations were measured using the wavefront analyzer KR-1W (Topcon) and their correlation with decentration were analyzed. Coma, spherical, 3rd-, 4th-order, trefoil, tetrafoil aberrations, ocular, and internal higher-order aberrations were calculated for a 4.0 mm pupil diameter. Results. The mean age of patients was 33.6 ± 21.4 years (ranging from 7 to 72 years). The mean follow-up period was 28.2 ± 10.5 months (ranging from 12 to 52 months). The mean postoperative best-corrected visual acuity (BCVA) was 0.19 ± 0.19 logMAR (range −0.18–0.52). The mean decentration was 0.57 ± 0.28 mm (range 0.15–1.21 mm). There was no correlation between Artisan IOL decentration and ocular higher-order aberrations, internal higher-order aberrations, coma, spherical, 3rd-, 4th-order, trefoil, and tetrafoil aberrations, respectively. There was a positive correlation between Artisan IOL decentration and 2nd-astig aberrations when 2nd-astig aberrations were less than 0.1. Conclusions. The position of Artisan IOLs showed slight decentration and the amounts of decentration were not large enough to influence higher-order aberrations.